KALIBRASI PARAMETER HIDROGRAF SATUAN SINTETIK NAKAYASU (STUDI SUNGAI-SUNGAI DI SULAWESI SELATAN ) - MUHAMAD YAMIN; BAGUS WIDHI DHARMA S (GANEC SWARA, 2019)
Many synthetic unit hydrographs have been developed including the Nakayasu Synthetic Hydriograph based on empirical observations in Japan. Although the determination of parameters has been presented with various criteria, so far the results are still relatively distorted if applied to watersheds in Indonesia, so it is necessary to calibrate some of the parameters used.   This research is a research study conducted in 3 sub-watersheds in South Sulawesi Province by using a type of spread, namely the Maros sub-watershed, Tallo sub-watersheds and Jeneberang sub-watersheds. There are 2 parameters to be calibrated, namely the coefficient α and Ctg with tg = 0.04-0.0058L, the calibration done is obtained α and Ctg values corresponding to each watershed.   The results of the study indicate that the use of the Nakayasu method for the purposes of the analysis of flood hydrographs which is a change in the variety of rainfall data in Indonesia, needs to be modified, especially to the parameters used. To get a range of parameters based on the parameters of watershed characteristics, it is necessary to conduct further studies on many watersheds based on the type of watershed.